Antibacterial and anti-biofilm activity of radezolid against Staphylococcus aureus clinical isolates from China - Wang, Cong; Xiong, Yanpeng; Bao, Chai; Wei, Ying; Wen, Zewen; Cao, Xinyi; Yu, Zhijian; Deng, Xiangbing; Li, Guiqiu; Deng, Qiwen (Frontiers in Microbiology, 2023)
Abstract The potent antibacterial ability of radezolid against Staphylococcus aureus has been widely reported worldwide, whereas its antibacterial and anti-biofilm activity against the S. aureus clinical isolates from China remain elusive. In this study, the minimum inhibitory concentration (MIC) of radezolid was determined in S. aureus clinical isolates from China by agar dilution method and the relationship of radezolid susceptibility with ST distribution were also investigated. The anti-biofilm activity of radezolid against S. aureus was determined by crystal violet assay and compared with that of linezolid and contezolid. The quantitative proteomics of S. aureus treated with radezolid was analyzed and the genetic mutations in radezolid-induced resistant S. aureus were determined by whole genome sequencing. The dynamic changes of transcriptional expression levels of several biofilm-related genes were analyzed by quantitative RT-PCR. Our data showed the range of radezolid MIC was from ≤0.125mg/L to 0.5 mg/L and that almost was 1/4× MIC of linezolid against S. aureus, indicating the greater antibacterial activity of radezolid than linezolid. The S. aureus clinical isolates with radezolid MICs of 0.5 mg/L were most widely distributed in ST239 of MRSA and ST7 of MSSA. Moreover, the more robust anti-biofilm activity of radezolid with sub-inhibitory concentration (1/8× MIC and1/16× MIC) were demonstrated against S. aureus when compared with that of contezolid and linezolid. Genetic mutations were found in glmS, 23S rRNA and DUF1542 domain-containing protein in radezolid induced resistant S. aureus selected by in vitro induction of drug exposure. Quantitative proteomic analysis of S. aureus indicated the global expression of some biofilm-related and virulence- related proteins were down-regulated. Quantitative RT-PCR further confirmed that the expressions of some down-regulated biofilm-related proteins, including sdrD, carA, sraP, hlgC, sasG, spa, sspP, fnbA and oatA, were decreased after 12 h and 24 h of exposure to radezolild. Conclusively, radezolid shows the robust antibacterial and anti-biofilm activity against S. aureus clinical isolates from China when compared with contezolid and linezolid.